Answer:
(f - g)(x) = -8x²
(f - g)(2) = -32
General Formulas and Concepts:
<u>Algebra I</u>
Step-by-step explanation:
<u>Step 1: Define</u>
f(x) = -10x² - x
g(x0 = -2x² - x
(f - g)(x) is f(x) - g(x)
(f - g)(2) is f(2) - g(2)
<u>Step 2: Find (f - g)(x)</u>
- Substitute: (f - g)(x) = -10x² - x - (-2x² - x)
- Distribute -1: (f - g)(x) = -10x² - x + 2x² + x
- Combine like terms: (f - g)(x) = -8x²
<u>Step 3: Evaluate</u>
- Substitute: (f - g)(2) = -8(-2)²
- Evaluate: (f - g)(2) = -8(4)
- Multiply: (f - g)(2) = -32
And we have our answers!
Answer:
5x2
Step-by-step explanation:
x(5x)
=x*5*x
=5*x2
=5x2
<h3>
Answer:</h3>
![a_n=4(-2)^{n-1}](https://tex.z-dn.net/?f=a_n%3D4%28-2%29%5E%7Bn-1%7D)
<h3>
Step-by-step explanation:</h3>
The common ratio is -8/4 = -2. The general formula for the n-th term is ...
... an = a1·r^(n-1) . . . . . . note the use of the caret (^) and parentheses
For r = -2 and a1 = 4, this becomes ...
... an = 4·(-2)^(n-1) . . . . approximately matches the 2nd selection
Answer:
x = 4
y = 3
Step-by-step explanation:
x = 10 - 2 y
substitute x = 10 - 2y into 2x - y = 5
20- 5y = 5
then
y = 3
and
x = 4
Mark brainliest
First, lets solve f(x). g(x) is already given. Find the slope of f(x) by doing m = y2-y1/x2-x1. I'm going to use -1,-5 (1) and 0,-1 (2). -1-(-5) = 4 and 0-(-1) = 1. This means that the slope is 4 since 4/1 = 4.
Now find y intercept (b). Since we know that y=4x+b, we can solve this by plugging in an ordered pair. I will use -1,-5. -5 = 4(-1) +b. With this, we see that -5 = -4+b and b = -1 since -5 = -4-1.
Your equation for f(x) is y=4x-1.
A: The slopes are equal since both of them are 4.
B: g(x) has a greater y intercept since 3 > -1.